Interaction of Virus Populations with Their Hosts - Domingo, Esteban (Virus as Populations, 2016)
Viral population numbers are extremely large compared with those of their host species. Population bottlenecks are frequent during the life cycle of viruses and can reduce viral populations transiently to very few individuals. Viruses have to confront several types of constraints that can be divided in basal, cell-dependent, and organism-dependent constraints. Viruses overcome them exploiting a number of molecular mechanisms, with an important contribution of population numbers and genome variation. The adaptive potential of viruses is reflected in modifications of cell tropism and host range, escape to components of the host immune response, and capacity to alternate among different host species, among other phenotypic changes. Despite a fitness cost of most mutations required to overcome a selective constraint, viruses can find evolutionary pathways that ensure their survival in equilibrium with their hosts.